2019
DOI: 10.1128/aac.02505-18
|View full text |Cite
|
Sign up to set email alerts
|

Natamycin and Voriconazole Exhibit Synergistic Interactions with Nonantifungal Ophthalmic Agents against Fusarium Species Ocular Isolates

Abstract: The in vitro activities of two antifungal drugs in combination with four nonantifungal ophthalmic agents were evaluated using a broth microdilution method and a collection of eight Fusarium ocular isolates that exhibited resistance to both natamycin (MICs, 14 to 32 μg/ml) and voriconazole (MICs, 4 to >128 μg/ml). Synergistic and indifferent interactions were observed for natamycin and 5-fluorouracil and natamycin with timolol dependent on the Fusarium isolate tested. Isolate-dependent synergistic and indiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In the theory of depletion, the interaction between fluconazole and amphotericin B would result in antagonism due to pre-exposure to fluconazole, which would lead to depletion of the membrane ergosterol, and thus there would be a decrease in the available sites for amphotericin B. In the second theory, the synergism, amphotericin B would lead to the formation of pores, which would facilitate the greater access of azole to the intracellular space, which by inhibiting the enzymes involved in ergosterol biosynthesis would increase the antimicrobial Echinocandin + azole Invasive candidiasis [157] AMP B + flucytosine Invasive candidiasis [158] Natamycin + 5-fluorouracil Fusarium species ocular isolates [159] AMP B: amphotericin B. Table 2.…”
Section: Synergistic Action Between Phytochemicals and Antifungalsmentioning
confidence: 99%
“…In the theory of depletion, the interaction between fluconazole and amphotericin B would result in antagonism due to pre-exposure to fluconazole, which would lead to depletion of the membrane ergosterol, and thus there would be a decrease in the available sites for amphotericin B. In the second theory, the synergism, amphotericin B would lead to the formation of pores, which would facilitate the greater access of azole to the intracellular space, which by inhibiting the enzymes involved in ergosterol biosynthesis would increase the antimicrobial Echinocandin + azole Invasive candidiasis [157] AMP B + flucytosine Invasive candidiasis [158] Natamycin + 5-fluorouracil Fusarium species ocular isolates [159] AMP B: amphotericin B. Table 2.…”
Section: Synergistic Action Between Phytochemicals and Antifungalsmentioning
confidence: 99%
“…Our overall goal was to test the feasibility of using a CRISPR/Cas9 system for targeted gene replacement in a corneal isolate from the U.S., identified initially as Fusarium by culture and then placed within the FSSC by ITS sequencing [28]. For this study, we further identified the isolate as FSSC 1 ( F. petroliphilum ) by performing a BLASTn of the tef-1 locus against the Fusarium -ID database.…”
Section: Resultsmentioning
confidence: 99%
“…All experiments were conducted with a clinical FK isolate (06-0110) from UCSF, previously identified as FSSC based on ITS sequencing [28]. Species-level identification was carried out by amplifying the tef-1 locus with universal primers [29].…”
Section: Methodsmentioning
confidence: 99%
“…Combination therapy of natamycin with voriconazole, itraconazole or micafungin showed synergism,76 although Prajna et al reported in a clinical trial equal or inferior efficacy of 1% voriconazole compared to 5% natamycin alone in eye drops 77. Rees et al evaluated in vitro activities of natamycin and voriconazole in combination with four non-antifungal ophthalmic agents (5-fluorouracil, dorzolamide, EDTA and timolol) 78. In eight Fusarium ocular isolates, resistance was noted to both natamycin and voriconazole.…”
Section: Current and New Drugs In The Pipelinementioning
confidence: 99%
“…In eight Fusarium ocular isolates, resistance was noted to both natamycin and voriconazole. The data suggested that commonly used ophthalmic agents enhance the in vitro activity of antifungal drugs against drug-recalcitrant ocular fusariosis when used in combination 78. Posaconazole and ravuconazole are new azoles that have yet to be topically applied in ophthalmic settings.…”
Section: Current and New Drugs In The Pipelinementioning
confidence: 99%